Pengetahuan Tidak Berhubungan dengan Sikap Keluarga tentang Kejadian Pernikahan Usia Dini di Kelurahan Lombang-Lombang Kabupaten Mamuju - Swarjana, I Kadek Dwi; Tarnoto, Tenny; Sitoresmi, Hayyu; Wahida, Nurul (Mando Care Jurnal, 2025)
Early marriage is a significant social issue in Indonesia, with widespread impacts on individuals’ health, education, and welfare. This study aims to examine the relationship between the level of knowledge and family attitudes regarding the occurrence of early marriage. The method used in this study is quantitative research with a cross-sectional approach. The study sample consisted of 50 respondents selected using a total sampling technique. Data were collected using a questionnaire measuring families’ knowledge and attitudes about early marriage. Statistical analysis was performed using the chi-square test. The results showed that out of 50 respondents, 38 (76%) had a good level of knowledge, and 48 (94%) exhibited a positive attitude. It can be concluded that there is no significant relationship between knowledge and family attitudes toward early marriage, with a p-value of 0.53, which is greater than the significance level α = 0.05. It is recommended that future research design more effective intervention programs to reduce the incidence of early marriage in the community.